Differentiating borderline and antisocial personality disorders in forensic settings. Issue 2 (7th February 2022) - Anderson, Jaime L.; Burchett, Danielle; Glassmire, David M.; Wygant, Dustin B.; Kamphuis, Jan H.; Smid, Wineke; Sellbom, Martin
ABSTRACT: The current study examined the differentiation of borderline (BPD) and antisocial personality disorders (ASPD) in forensic settings, with particular emphasis on the utility of the MMPI-2-RF in differential diagnosis. This study examined these constructs across correctional and forensic psychiatric samples from the U.S. and the Netherlands using varying assessment/diagnosis modalities, including self-report, structured interview, and clinician-derived personality disorder (PD) diagnosis from both DSM-5 Section II and Section III perspectives. Our findings showed that internalizing psychopathology – and to a lesser extent interpersonal and thought dysfunction – differentiated BPD from ASPD; however, inconsistencies existed across samples. Higher levels of externalizing psychopathology were not found to differentiate ASPD across any of the samples or PD conceptualizations used in the current study. This suggests that diagnostic clarity may be particularly difficult in forensic settings and supports previous work that has shown problematic diagnostic overlap and a lack of differentiation between PD constructs. Nonetheless, as our current diagnostic system continues to rely on categorical determination of PDs, the current study suggests the MMPI-2-RF may enhance diagnostic differentiation.